Agarwood Production - A Multidisciplinary Field to be Explored in Bangladesh - Akter, Selina; Islam, Md Tavir; Zulkefeli, Mohd; Khan, Sirajul Islam (International Journal of Pharmaceutical and Life Sciences, 2013)
Agarwood or eaglewood (Aguru in Bengali) is the most expensive wood in the world, which is an occasional product of a few genera of Aquilaria and Gyrinops in the plant family Thymelaeaceae. Agar is a scented product, oleoresin, obtained from pathological conditions of the wood of live trees containing many aromatic substances. Various bacteria and fungi have been found to be associated with Agarwood formation, although it is still not absolutely clear which are important or even necessary. The quality of agar mostly depends on the plant species and the fungal species involved, as well as, certain other unknown factors. The issues are now to explore the new sources of agarwood to protect the endangered plant species, to ensure agar formation in 100% of the planted trees, upgrade in quality and most possibly quantity of agar yield per tree simultaneously minimizing the maturation time. Both physical and chemical stresses like mechanical wound and induction have long been practiced to enhance agarwood yield as well as fungal inoculation. Specificity of fungal infection is a minor criterion of agarwood formation rather than the plants physiological state, immune responses and presence of inducer. The agarwood production could be a multifaceted field of prospects in Bangladesh. The cultivation of new Aquilaria and Gyrinops plants and selection of appropriate inocula and inducers should be the priority objective. A multidisciplinary approach could be initiated with the experts of forestry, mycology, biochemistry and microbiology to achieve the goal. DOI: http://dx.doi.org/10.3329/ijpls.v2i1.15132 International Journal of Pharmaceutical and Life Sciences Vol.2(1) 2013: 22-32